Star polymers rupture induced by constant forces - García, Nicolás (2014)
In this work, we study the breakage process of an unknotted three-arm star-shaped polymer when it is pulled from its free ends by a constant force. The star polymer configuration is described through an array of monomers coupled by anharmonic bonds, while the rupture process is tracked in three-dimensional space by means of Langevin Molecular Dynamics simulations. The interaction between monomers is described by a Morse potential, while a Weeks-Chandler-Anderson energetic contribution accounts for the excluded volume interaction. We explore the effect of the molecular architecture on the distributions of rupture times over a broad interval of pulling forces and star configurations. It was found that the rupture time distribution of the individual star arms is strongly affected by the star configuration imposed by the pulling forces and the length of the arms. We also observed that for large pulling forces the rupture time distributions resemble the dominant features observed for linear polymer chains. The model introduced here provides the basic ingredients to describe the effects of tensile forces on stress-induced degradation of branched macromolecules and polymer networks.